Bioethics for the 21st century: building hope - Adela Cortina (Revista Iberoamericana de Bioética, 2016)
Bioethics faces the challenge of collaborating in building a just and sustainable world. This article analyzes the birth of bioethics as a civic bioethics of pluralistic societies in the context of applied ethics, its evolution to become a global bioethics, its current structure, the challenges it faces, and finally the kind of practical reasoning that should guide its task if bioethics is to achieve its goals.